The impact of television programme on the mindset and attitudes of youths in the rural areas. - Osman, Mohd Nizam (Pacific and Asian Communication Association, 2010)
Issues on the role of television as a medium of education and persuasion, apart from entertainment and information gathering have been widely discussed and debated by researchers in the past (see for example, Zajonc 1968, Tan, Fujioka & Tan 2001, Mastro & Tropp 2004). In this case, television is seen as a medium that is capable of positively educating and influencing the attitudes and mindset of the viewers. This assumption is consistent with the Cultivation Theory which provides the assumption that television is indeed capable of influencing the attitudes of the viewers. As a means of addressing the reliability of the assumptions derived from past studies indicating that television is perceived to be a powerful socialization agent of change among viewers, this study therefore is carried out among television viewers residing in rural areas in the state of Sabah, in Malaysia. The questionnaire survey method has been administered for the study, involving a total of 224 respondents residing in the rural parts of Sabah who have been asked to provide their reactions as to what extent television programming are capable of positively influencing and changing their mindset. The findings of the study will be presented and discussed using the descriptive statistics approach based on the frequency and percentage tabulation.